1995
DOI: 10.1002/bjs.1800820207
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of appendicectomy versus antibiotic therapy for acute appendicitis

Abstract: In a prospective controlled study the effect of antibiotics as the only treatment in acute appendicitis was evaluated. Of 40 patients admitted with a duration of abdominal pain of less than 72 h, 20 received antibiotics intravenously for 2 days followed by oral treatment for 8 days and 20 considered as controls were randomized to surgery. All patients treated conservatively were discharged within 2 days, except one who required surgery after 12 h because of peritonitis secondary to perforated appendicitis. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
360
1
16

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(384 citation statements)
references
References 10 publications
7
360
1
16
Order By: Relevance
“…Five prospective RCTs [27][28][29][30][31] with a total of 1430 patients met the selection criteria and were eligible for inclusion. The number of patients, per protocol, allocated to the antibiotic group was 644, while 786 patients comprised the surgery group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five prospective RCTs [27][28][29][30][31] with a total of 1430 patients met the selection criteria and were eligible for inclusion. The number of patients, per protocol, allocated to the antibiotic group was 644, while 786 patients comprised the surgery group.…”
Section: Resultsmentioning
confidence: 99%
“…The most recent RCTs used ertapenem, following the previously published guidelines by the surgical infection society and the infectious diseases society of America for the management of intra-abdominal infection [34]. As for post-discharge antibiotics, four of the five selected studies used a combination of a second or third generation fluoroquinolone; ofloxacin, ciprofloxacin or levofloxacin, and a nitroimidazole; metronidazole or tinidazole [27][28][29]31]. Vons et al continued to use amoxicillin and clavulinic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Disseminated intra-abdominal infection from appendicitis, however, is not seen as often today as in the first decades of the 20th century, when appendicitis was the major cause of severe peritonitis and peritonitis-related mortality (36,37,38). Although antibiotics may be used as primary treatment for selected patients with suspected uncomplicated appendicitis, appendectomy is still the gold standard therapy for acute appendicitis (36,37,38). Treatment includes source control by appendectomy, rarely in the most severe cases staged abdominal repair in cases when peritoneal edema has led to abdominal compartment syndrome.…”
Section: Source Control Of Appendix Perforationmentioning
confidence: 99%
“…Treatment includes source control by appendectomy, rarely in the most severe cases staged abdominal repair in cases when peritoneal edema has led to abdominal compartment syndrome. Studies have demonstrated that antibiotics alone may be useful to treat patients with early, non perforated appendicitis, even if there is a risk of recurrence (36,37,38). Randomized clinical trial by Hanson et al compared antibiotic therapy versus appendectomy as primary treatment of acute appendicitis (39).…”
Section: Source Control Of Appendix Perforationmentioning
confidence: 99%
“…1,2 It remained the gold standard for the next century. However, the introduction of laparoscopic appendectomy in the 1980s advanced the tide of change toward minimally invasive surgery.…”
mentioning
confidence: 99%